The misadventures of Maude March, or, Trouble rides a fast horse [compact disc, unabridged] - Couloumbis, Audrey (Random House Audio, Listening Library, 2006)
After the death of the stern aunt who raised them since they were orphaned, eleven-year-old Sallie and her fifteen-year-old sister escape their self-serving guardians and begin an adventure resembling those in the dime novels Sallie loves to read.